High Growth Aspirations of Nascent Entrepreneurs: Why Do They Fall? - Krzysztof Zięba (Studia i Materiały)
Intention-based research becomes more and more popular in various domains, including entrepreneurship. Achieving growth by a business must be planned or at least consciously accepted by the business owner. That is why it is vital to take growth intentions into account when trying to predict growth of business. Personal attitude of an entrepreneur towards growth is important from the very beginning of business operations or even before that. Nascent entrepreneurs also have their growth aspirations during the business founding process, and those aspirations affect both this process and the subsequent growth of a new business. The aim of this paper is to investigate growth aspirations of nascent entrepreneurs in comparison to the attitudes of actual entrepreneurs towards the growth of their businesses. Additionally, this paper offers indirect answers to the question on what kind of mechanism – Lamarckian adaptation or Darwinian negative selection – may be responsible for a gradual lowering of growth aspirations expressed by nascent entrepreneurs.